2011
DOI: 10.1096/fj.10-172981
|View full text |Cite
|
Sign up to set email alerts
|

Wnt1 is a proangiogenic molecule, enhances human endothelial progenitor function, and increases blood flow to ischemic limbs in a HGF‐dependent manner

Abstract: Human endothelial progenitor cells (hEPCs) participate in neovascularization of ischemic tissues. Function and number of hEPCs decline in patients with cardiovascular disease, and therapeutic strategies to enhance hEPC function remain an important field of investigation. The Wnt signaling system, comprising 19 lipophilic proteins, regulates vascular patterning in the developing embryo. However, the effects of Wnts on hEPCs and the adult vasculature remain unclear. We demonstrate here that Wnt1 is expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Several factors might contribute to this clinically relevant anti-angiogenic role of WIF1 such as: (1) a decrease in VEGF transcription caused by a decrease in nuclear b-catenin, a known promoter of angiogenesis by an increase in VEGF expression (Skurk et al, 2005); (2) a decrease in VEGF half-life because of a decrease in CD44, a well-established proteolysis inhibitor of VEGF (Jones et al, 2000); (3) an increase in p53 expression, as the loss of p53 has been correlated with an increased VEGF expression and tumor angiogenesis (Linderholm et al, 2001); (4) a decrease in WNT1, a protein shown to stimulate the proliferation and angiogenic functions of human endothelial cells (Wright et al, 1999;Gherghe et al, 2011); and (5) a decrease in the endothelial cell-cell adhesion molecule CD31, a protein required for neovascularization (DeLisser et al, 1997). In early-stage cervical cancer, CD31 expression is significantly associated with lymphatic vascular space invasion and tumor size (Silva-Filho et al, 2006).…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachanmentioning
confidence: 99%
“…Several factors might contribute to this clinically relevant anti-angiogenic role of WIF1 such as: (1) a decrease in VEGF transcription caused by a decrease in nuclear b-catenin, a known promoter of angiogenesis by an increase in VEGF expression (Skurk et al, 2005); (2) a decrease in VEGF half-life because of a decrease in CD44, a well-established proteolysis inhibitor of VEGF (Jones et al, 2000); (3) an increase in p53 expression, as the loss of p53 has been correlated with an increased VEGF expression and tumor angiogenesis (Linderholm et al, 2001); (4) a decrease in WNT1, a protein shown to stimulate the proliferation and angiogenic functions of human endothelial cells (Wright et al, 1999;Gherghe et al, 2011); and (5) a decrease in the endothelial cell-cell adhesion molecule CD31, a protein required for neovascularization (DeLisser et al, 1997). In early-stage cervical cancer, CD31 expression is significantly associated with lymphatic vascular space invasion and tumor size (Silva-Filho et al, 2006).…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachanmentioning
confidence: 99%
“…Likewise, active Wnt/LRP receptor/beta-catenin signaling is necessary for the function of EC progenitors 62, 85 and -- with BMP / ALK receptor/ Smad pathways – it promotes the endothelial-mesenchymal transition (EnMT) necessary to create cardiac valves 86 and epicardial fibroblasts 87 . These same morphogenetic pathways appear to participate in the pathobiology of cardiovascular calcification and post-natal valve homeostasis.…”
Section: Morphogens and The Pathobiology Of Cavdmentioning
confidence: 99%
“…A proto-oncogene protein Wnt1 can induce tumor growth and angiogenesis [53,54]. With regards to lymphangiogenesis, however, a recent study showed that Wnt1 could protect against melanoma progression by suppressing melanoma-derived VEGF-C expression, followed by reduced lymphangiogenesis and metastasis [55].…”
Section: Regulation Of Vegf-c Gene Expressionmentioning
confidence: 99%